Investigation on the electrical performances and stability of W-doped ZnO thin-film transistors. (1st June 2019) - Abliz, Ablat; Wan, Da; Yang, Linyu; Mamat, Mamatrishat; Chen, Henglei; Xu, Lei; Wang, Chunlan; Duan, Haiming
Abstract: In this work, W-doped ZnO thin films and devices were fabricated by RF magnetron sputtering processes. The electrical properties and stability of W-doped ZnO thin film transistors (TFTs), and the structural and electrical of W-doped ZnO thin film were investigated as a function of W doping concentration. As a result, a reasonable field effect mobility of 9.2 cm 2 /V s, current on/off ratio of 10 6, low threshold voltage of 4.5 V and small subthreshold slope of 0.36 V/decade were simultaneously achieved. Moreover, the devices exhibit high stability with small threshold voltage shifts of − 1.8 V under negative bias stress for 60 min without any passivation layer. The X-ray photoelectron spectrometry and Hall measurement characterizations indicate that the carrier concentration, oxygen vacancy defects and total trap density were efficiently reduced by W doping concentration. Our results suggest that W doping is an effective method to achieve high performance in ZnO thin film transistors. Therefore, the approach present here should be feasible for good stability and low-cost indium free oxide TFTs in flat panel displays. Graphical abstract: fx1 Highlights: The oxygen vacancy of ZnO film is reduced by W doping concentration. The W doping have enhanced stability of ZnO TFTs. The total trap density of ZnO TFTs is reduced by W doping concentration.